The barriers and enablers to implementing the New South Wales Healthy School Canteen Strategy in secondary schools in the Illawarra and Shoalhaven regions – A qualitative study. (25th August 2021) - Johnston, Rosi; Norman, Jennifer; Furber, Susan; Parkinson, Julie
Abstract: Issue addressed: In 2017, the New South Wales Healthy School Canteen Strategy (Strategy) was introduced into primary and secondary schools. Studies have reported that secondary schools have a lower level of compliance with healthy canteen policies compared with primary schools. This study aims to identify and describe the barriers and enablers to implementing the Strategy in Department of Education (DoE) secondary schools in the Illawarra and Shoalhaven regions. Methods: The framework underpinning the study was the systems theory. Canteen managers (CM) and principals from the 21 DoE secondary schools in the Illawarra and Shoalhaven regions were invited to participate in semi‐structured interviews. The interviews were structured around the five focus areas of the Strategy, including questions on school nutrition policies and the role of the canteen. Data were collated using the interview guides as a framework and qualitative content analysis, using manual coding, was undertaken. Results: Eight (38%) schools participated with seven CMs and six principals interviewed. Barriers to implementing the Strategy included the changing role of the canteen, the increased demands placed on CMs and inconsistencies between the school food environment and the Strategy. Enablers included monitoring implementation, and internal and external support. This study also recognised that previously identified barriers to healthy canteen strategy implementation are ongoing. Conclusions: The school canteen is an integral part of the school environment and therefore needs whole‐of‐school support if successful implementation of the Strategy is to occur. So what: Addressing the barriers and promoting the enablers identified in this study will support better nutrition policy implementation in secondary schools.